SISTEM INFORMASI MANAJEMEN DALAM PELAYANAN PUBLIK DI KANTOR CATATAN SIPIL KOTA TOMOHON - RAHEL TUMEWU; JOYCE RARES; JOORIE RURU (JURNAL ADMINISTRASI PUBLIK, 2022)
Public service is basically is an action or advantage that offered to another part and basically has no formthat can be feel or experienced and that means is service is some kind of product that makes this product isunreal and cant be feel. So the government have to make sure for building trust to public that of courseneeded effort to make it that happen and need extra effort for gaining public trust to the government and formaking the public feel that they got the best service from government because as citizen they have a rights togot the best public service, management information system itself is a one of the factor or support that canmake public servie become more efficient and effective because the system use technology as one of the partof the system management information system itself is activity that provide informationKeyword : Information System,Management,Public Service